Maternal Uniparental Isodisomy of Chromosome 2 Leading to Homozygous Variants in SPR and ZNF142: A Case Report and Review of the UPD2 Literature - Kelkar, Janhawi; DiMaio, Miriam; Ma, Deqiong; Zhang, Hui (Global medical genetics, 2024)
We report a 4-year-old girl with neurodevelopmental abnormalities who has maternal uniparental isodisomy of chromosome 2 leading to homozygosity for a likely pathogenic variant in SPR, and a variant of uncertain significance in ZNF142. Biallelic pathogenic variants in SPR lead to sepiapterin reductase deficiency (SRD), a dopa-responsive dystonia. Pathogenic variants in ZNF142 are associated with an autosomal recessive neurodevelopmental disorder characterized by impaired speech and hyperkinetic movements, which has significant clinical overlap with SRD. Our patient showed dramatic improvement in motor skills after treatment with levodopa. We also reviewed 67 published reports of uniparental disomy of chromosome 2 (UPD2) associated with various clinical outcomes. These include autosomal recessive disorders associated with loci on chromosome 2, infants with UPD2 whose gestations were associated with confined placental mosaicism for trisomy 2 leading to intrauterine growth restriction with good postnatal catchup growth, and normal phenotypes in children and adults with an incidental finding of either maternal or paternal UPD2. These latter reports provide support for the conclusion that genes located on chromosome 2 are not subject to imprinting. We also explore the mechanisms giving rise to UPD2.